1000-Year Quasi-Periodicity of Weak Monsoon Events in Temperate Northeast Asia since the Mid-Holocene. Issue 1 (December 2017) - Jo, Kyoung-nam; Yi, Sangheon; Lee, Jin-Yong; Woo, Kyung; Cheng, Hai; Edwards, Lawrence; Kim, Sang-Tae
Abstract The Holocene variability in the East Asian summer monsoon (EASM) based on speleothem δ18 O records has inconsistencies in timing, duration, and expression of millennial-scale events among nearby regions, and even within the same cave. Here, we present another stalagmite δ18 O record with multi-decadal time resolution from the temperate Korean Peninsula (KP) for the last 5500 years in order to compare with Holocene millennial-scale EASM events from Southeast Asia. Based on our new stalagmite δ18 O record, millennial-scale events since the mid-Holocene were successfully identified in the KP, representing a noticeable cyclic pattern with a periodicity of around 1000 years. We propose that the Holocene millennial-scale events are common hydroclimatic phenomena at least in the East Asian monsoon system. Meanwhile, the shorter periodicity of millennial-scale events than that of the North Atlantic region is likely to decouple the EASM system from the North Atlantic climate system. This observation suggests that weak EASM and North Atlantic Bond events may have been induced independently by direct solar activity (and then possible feedback) and ocean–ice sheet dynamics, respectively, rather than simple propagation from the North Atlantic to the EASM regions.